Ro-Mantis: lounge chair/ Eqbal Naqib Elmi-Rizal - Elmi-Rizal, Eqbal Naqib (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Nature has always been a source of inspiration for the human. Human observed and tried to learn about natural forms and structures. Designers have also observed how life proceeded in nature and began to develop the furniture by observing or imitating the natural structures. Nature gave them plenty of opportunities with its admirable mechanisms, designs and potential to enrich a various aspect of life. To achieve the objective of design and produce furniture (chair) inspired by nature for residential area, the designer narrowed down into three main nature inspired concept as subject matter which are butterfly, wave and mantis. Research has been conducted to study the characteristic or detail of the nature inspired concept and the designer selected mantis as the main concept. The design of the furniture focuses on the issues that have been found during research process through survey in google form. It includes what the respondents preferred which are to add on a suitable features, design a better posture and support on the back rest for relaxing and enhance the comfortability for the head rest. As a result, the designer designed Romantis as a lounge chair for living room that inspired by mantis in a standing form. The lounge chair provided a triangular head rest and have a cup holder features on both side. Moreover, the leg and arm rest of the chair use round hollow metal bending to adapt long skinny legs of mantis. This chair is made out of cotton fabric as upholstery to maintain the comfortability in South East Asia temperature. The design more towards curvy shape and the combination of wood, plastic and metal material emphasize the hi-tech partial style.